Distinctive Sounds System in Mehri Language Used in Al- Wasaa’, Saudi Arabia - Alotaibi, Hind Jaza; Al- Azraqi, Munira Ali (Journal of Humanities & Social Sciences, 2019)
This research aims to examine the sounds in the Mehri language in Al- Wasaa’ in the eastern region of Saudi Arabia that has no counterparts in Arabic sounds. The study primarily depends on a descriptive and analytical approach which lies upon describing the distinctive sounds. By interviewing six females (aged 17 to 60). In order to know different aspects of their live, eight males (aged 14 to 60) were interviewed, some of them were educated and others are not, who are living in Al- Wasaa’. The findings of the research revealed five sounds that have no counterparts in the Arabic language which are ṣ, ṣ́, ḳ, ź, ś consonants in Mehri language.